Genetic and environmental risk factors in the non‐medical use of over‐the‐counter or prescribed analgesics, and their relationship to major classes of licit and illicit substance use and misuse in a population‐based sample of young adult twins - Gillespie, Nathan A.; Bates, Timothy C.; Hickie, Ian B.; Medland, Sarah E.; Verhulst, Brad; Kirkpatrick, Robert M.; Kendler, Kenneth S.; Martin, Nicholas G.; Benotsch, Eric G. (Addiction, 2019)
Background and Aims: The non‐medical use of over‐the‐counter or prescribed analgesics (NMUA) is a significant public health problem. Little is known about the genetic and environmental etiology of NMUA and how these risks relate to other classes of substance use and misuse. Our aims were to estimate the heritability NMUA and sources of genetic and environmental covariance with cannabis and nicotine use, cannabis and alcohol use disorders and nicotine dependence in Australian twins. Design Biometrical genetic analyses or twin methods using structural equation univariate and multivariate modeling. Setting: Australia. Participants: A total of 2007 young adult twins [66% female; μage = 25.9, standard deviation (SD) = 3.6, range = 18–38] from the Brisbane Longitudinal Twin Study retrospectively assessed between 2009 and 2016. Measurements: Self‐reported NMUA (non‐opioid or opioid‐based), life‐time nicotine, cannabis and opioid use, DSM‐V cannabis and alcohol use disorders and the Fagerström Test for Nicotine Dependence. Findings Life‐time NMUA was reported by 19.4% of the sample. Univariate heritability explained 46% [95% confidence interval (CI) = 0.29–0.57] of the risks in NMUA. Multivariate analyses revealed that NMUA is moderately associated genetically with cannabis (rg = 0.41) and nicotine (rg = 0.45) use and nicotine dependence (rg = 0.34). In contrast, the genetic correlations with cannabis (rg = 0.15) and alcohol (rg = 0.07) use disorders are weak. Conclusions: In young male and female adults in Australia, the non‐medical use of over‐the‐counter or prescribed analgesics appears to have moderate heritability. NMUA is moderately associated with cannabis and nicotine use and nicotine dependence. Its genetic etiology is largely distinct from that of cannabis and alcohol use disorders.